In Silico and In Vitro Studies of Mycotoxins and Their Cocktails; Their Toxicity and Its Mitigation by Silibinin Pre-Treatment - Tran, Van Nguyen; Viktorova, Jitka; Augustynkova, Katerina; Jelenova, Nikola; Dobiasova, Simona; Rehorova, Katerina; Fenclova, Marie; Stranska-Zachariasova, Milena; Vitek, Libor; Hajslova, Jana; Ruml, Tomas (Toxins, 2020)
Mycotoxins found in randomly selected commercial milk thistle dietary supplement were evaluated for their toxicity in silico and in vitro. Using in silico methods, the basic physicochemical, pharmacological, and toxicological properties of the mycotoxins were predicted using ACD/Percepta. The in vitro cytotoxicity of individual mycotoxins was determined in mouse macrophage (RAW 264.7), human hepatoblastoma (HepG2), and human embryonic kidney (HEK 293T) cells. In addition, we studied the bioavailability potential of mycotoxins and silibinin utilizing an in vitro transwell system with differentiated human colon adenocarcinoma cells (Caco-2) simulating mycotoxin transfer through the intestinal epithelial barrier. The IC50 values for individual mycotoxins in studied cells were in the biologically relevant ranges as follows: 3.57-13.37 nM (T-2 toxin), 5.07-47.44 nM (HT-2 toxin), 3.66-17.74 nM (diacetoxyscirpenol). Furthermore, no acute toxicity was obtained for deoxynivalenol, beauvericin, zearalenone, enniatinENN-A, enniatin-A1, enniatin-B, enniatin-B1, alternariol, alternariol-9-methyl ether, tentoxin, and mycophenolic acid up to the 50 nM concentration. The acute toxicity of these mycotoxins in binary combinations exhibited antagonistic effects in the combinations of T-2 with DON, ENN-A1, or ENN-B, while the rest showed synergistic or additive effects. Silibinin had a significant protective effect against both the cytotoxicity of three mycotoxins (T-2 toxin, HT-2 toxin, DAS) and genotoxicity of AME, AOH, DON, and ENNs on HEK 293T. The bioavailability results confirmed that AME, DAS, ENN-B, TEN, T-2, and silibinin are transported through the epithelial cell layer and further metabolized. The bioavailability of silibinin is very similar to mycotoxins poor penetration.
Keywords: viabilita buněk; Cell Line; Mycotoxins; lékové interakce; silibinin; Comet Assay; Protective Agents; genotoxicity; acute toxicity; Computer Simulation; ochranné látky; Cell Survival; ostropestřec mariánský; cell protection; Silybin; potravní doplňky; ATP Binding Cassette Transporter, Subfamily B, Member 1; Coculture Techniques; Dietary Supplements; Animals; combined toxicity; lidé; P-glykoprotein; Humans; Drug Interactions; zvířata; kometový test; in silico prediction; myši; kokultivační techniky; buněčné linie; co-culture models; počítačová simulace; Mice; Silybum marianum; mykotoxiny